The use of cyclohexymide and chloramphenicol in raising the resistance of wheat plants triticum estivunz L. to cold and ablution - Mohammed Sadek; Ghareba Danial (College of Education for Pure Sciences, 2007)
Homogenized healthy seeds of Triticum aestivum L .Abo - Greab-3-cultivar were used to study the possibility of using a mixture of two protein synthesis inhibitors in Eukaryote and Prokaryote (cycloheximide and hloramphenicol )to increase cold and freezing tolerance of wheat . The study was designed as (3x3x3) Factorial experiment and carried -out with three replicates according to randomize complete block design (RCBD). The first factor was represented by the temperature which comprised 20,o,-5 C0 • The second factor was the concentration of the antibiotics mixture (cycloheximide chloramphenicol) which comprised 0:0,50}1g/mL:50 }lg/mL and 100 }lg/mL: 100 }lglmL. The third factor was the treatment periods which were 0, 12,and 24 hours . Different degrees of temperature showed significant effects at 0.05 level of significance in: plant height, nu .of tillers I plant ,nu. of spikes /plant ,length and weight of spikes and weight of 1000 grains. Different concenterations of cycloheximide and chloramphenicol mixture showed significant effects in :nu .of tillers /plant ,nu. of spikes/ plant ,weight of spikes ,nu. of grains /spikes and 1000 grains weight .Treatment periods showed significant effects in all studied parameters except in fresh and dry gluten. All the interactions among the studied factors were significant.